Paracetamol detection at a modified electrode based on platinum nanoparticles immobilized on Al-SBA-15 composite material - Thi Thanh Hien NGO; Ioana Carmen FORT; Thanh Huyen PHAM; Graziella Liana TURDEAN (My University, 2019)
Paracetamol detection at a modified electrode based on platinum nanoparticles immobilized on Al-SBA-15 composite material
Keywords: Modified electrode